(untitled) (Swiss Medical Weekly, 2014)
Live attenuated viral vaccines (LAVV) have been used safely and with great success for decades to protect healthy patients against sometimes life-threatening diseases. The current recommendations usually contraindicate their use in immunocompromised hosts, despite an often increased risk for a severe presentation of disease. In this article, we review currently available LAVV, such as varicella-zoster, measles/mumps/rubella, influenza, polio, rotavirus, and yellow fever in patients with solid organ or haematopoietic stem cell transplantation. The current paediatric and adult experience with pre- and post-transplantation vaccination is discussed. To date, because of insufficient data, evidence-based recommendations to safely vaccinate transplant recipients are not available. Hopefully in the near future, specific recommendations will be implemented for certain LAVV in these patients.